Challenges in Translation of English Phraseological Units With Onomastic Constituents Into Vietnamese Equivalents - Khoa, Nguyen Viet (VNU Journal of Foreign Studies; Vol 37 No 3DO - 10.25073/2525-2445/vnufs.4624, 2021)
Translation of phraseological units with proper names (PUPs) is topical for the contemporary translation studies nowadays. It is noted that PUPs reflect the culture and national mentality of a definite nation. Quite a few studies have prospectively examined English PUPs and their translation into other languages, but it is hard to find such an in-depth study in the case the target language is Vietnamese. By employing the qualitative approach, this paper sets out the findings of the study where 241 English PUPs in our compiled database were classified into four groups according to their translations into Vietnamese. The group of non-idiomatic and descriptive translation equivalents accounts for a majority of more than 57% of all the PUPs, proving that PUPs in both languages are highly culture-specific. Although the other three groups share a minority of approximately 43% of all the PUPs, they hold interesting implications and multiple levels of similar or different metaphors. Based on the findings, the paper discusses the challenges translators encounter during the translation process of English PUPs into their Vietnamese equivalents. It is evident that among various translation obstacles, the proper name factor is clearly one of the most challenging issues. The paper then proposes some translation solutions to cope with these special expressions. In addition to recommending to flexibly apply translation strategies, the author's conclusion emphasizes that only when translators manage to decode and grasp how PUPs work cross-linguistically in both languages and cultures can they achieve an appropriate translation of English PUPs.